Hubungan Stunting dengan Pengetahuan Ibu dan Asuhan Gizi di Aceh, Indonesia: The Correlation between Stunting, Maternal Knowledge, and Nutritional Care in Aceh, Indonesia - Ramadhan, Muhammad Fatih; Dimiati, Herlina; Hidayaturrahmi, Hidayaturrahmi; Indah, Rosaria (Universitas Airlangga, 2024)
Background: Aceh province is one of the Indonesian provinces with the highest prevalence of stunting. Many factors contribute to this situation, including maternal knowledge. Although many studies have been conducted in Indonesia, literature exploring the correlation between stunting, mothers’ knowledge of stunting, and nutritional care in the Aceh province is limited. Objectives: This study aimed to examine the correlation between mothers’ knowledge of stunting, nutritional care, and the prevalence of stunting. Methods: This study utilized a quantitative paradigm and a cross-sectional design. The participants were 90 mothers selected by purposive sampling technique at Neuheun village, a village with the highest stunting prevalence in Aceh Besar Regency. The data was collected using a questionnaire measuring the mothers’ knowledge of stunting and nutrition care. In addition, secondary data was collected based on the anthropometric measurements of the children from the local community health center. Results: The findings suggest a significant correlation between maternal knowledge and stunting prevalence (p-value=0.003), as well as a significant correlation between nutrition care knowledge and stunting prevalence (p-value<0.001). Conclusions: This study concludes a significant correlation between mothers’ knowledge, nutritional care, and the prevalence of stunting in children at Neuheun Village, Aceh Besar Regency. Such findings underscore the imperative for concerted efforts among stakeholders to enhance maternal understanding of stunting and promote optimal nutritional care practices.